2023
DOI: 10.1371/journal.pone.0281123
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet is protective against kidney injury in hypertensive-diabetic mice, but leads to liver injury

Abstract: Chronic kidney disease (CKD) is a worldwide health burden with increases risk of end-stage renal function if left untreated. CKD induced in the context of metabolic syndrome (MS) increases risks of hypertension, hyperglycemia, excess body fat and dyslipidemia. To test if combining a high-fat diet (HFD) regimen onto the hypertensive/ diabetic phenotype would mimic features of MS induced-CKD in mice, hyperglycemia was induced in genetically hypertensive mice (Lin), followed by HFD regimen. For that, 8-week-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Hyperglycemia impairs water reabsorption, leading to dehydration. LinSTZ mice had increased water intake compared to control Lin animals (Fig 1C and 1G), while urinating a volume equivalent to their body weight per day (Fig 1D and 1H), as observed previously observed by our research group [24,32]. CANA was able to reverse polydipsia and polyuria in male LinSTZ mice (Fig 1C and 1D), but not in females (Fig 1G and 1H).…”
Section: Plos Onesupporting
confidence: 85%
See 3 more Smart Citations
“…Hyperglycemia impairs water reabsorption, leading to dehydration. LinSTZ mice had increased water intake compared to control Lin animals (Fig 1C and 1G), while urinating a volume equivalent to their body weight per day (Fig 1D and 1H), as observed previously observed by our research group [24,32]. CANA was able to reverse polydipsia and polyuria in male LinSTZ mice (Fig 1C and 1D), but not in females (Fig 1G and 1H).…”
Section: Plos Onesupporting
confidence: 85%
“…Hyperglycemia is associated with dysregulated lipid metabolism and liver dysfunction [24,45,46]. In our study, we observed an increase in triglyceride (TG) levels in males LinSTZ, while CANA mice had lower levels TG compared to LinSTZ (Fig 4B).…”
Section: Plos Onesupporting
confidence: 51%
See 2 more Smart Citations